If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = 5x Solving 17 = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 17 + -5x = 5x + -5x Combine like terms: 5x + -5x = 0 17 + -5x = 0 Add '-17' to each side of the equation. 17 + -17 + -5x = 0 + -17 Combine like terms: 17 + -17 = 0 0 + -5x = 0 + -17 -5x = 0 + -17 Combine like terms: 0 + -17 = -17 -5x = -17 Divide each side by '-5'. x = 3.4 Simplifying x = 3.4
| 0=t(t+5) | | y^2-12y+20= | | -3X=32 | | 4b^2=20b | | w(10w+3)=7 | | x-(-3)=-12 | | 10x-2(x-5)=8x+2 | | (4x^2)y+8y=2x | | x+(x+1)+(x+2)=x^3+85 | | 1/3(2x+3)-1/5(x+6)=4 | | x(x+1)(x+2)=x^3+85 | | 5(2x-2)-5x=0 | | -(15-35)-(7s+1)=60 | | b^2=20b | | 16+9w=7+27w | | -40000x^2+8820x+190000=0 | | 12x+-5y=2 | | x^2=512 | | q=r+st | | 4x^2y-6xy^2+5xy= | | h=2gh | | 3(3k+5)-11k+5+5= | | 7x=5x | | 9s-100= | | -2p+7=6-(7p+8) | | -7x=-8 | | 2x+4=-2x+1 | | -2p+7=5-(7p+8) | | 49x=33 | | 57-(5x+3)=5(x+2)+x | | w^2=6(w-2) | | a/5-4=-3 |